Value Orientation as Structural Component of Personality in Mountain Regions - Lemko, Galina (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
This paper, presented at the Conference Plenary, is devoted to the problem of formation of values and value orientations of a personality in mountain regions. The author asserts that value orientation in mountain regions is a complex formation, which includes different levels and forms of interaction of public and individual personality. The article also regards and analyzes the hierarchy of values. It is mentioned that the personality value orientations in mountain regions don’t only determine the motivation of individual behavior but also forms his world outlook. The special attention is also devoted to the pseudo-values. The author points out that they do not contribute to human self-realization. The article also analyzes the reasons of forming of the value orientation in mountain regions and gives the classification of people in accordance with the commitment to certain values. The author touches the problem of cultural values of modern youth, the influence of electronic mass media and comes to the conclusion that classical culture begins to lose value and attractiveness. In conclusion the author says that the valued orientations in mountain regions occupy the central place in the psychical adjusting of man’s behavior. That is why considerable attention is spared to the study of valued-semantic sphere of personality on the modern stage of development of pedagogical science.